Biosurveillance of Selected Pathogens with Zoonotic Potential in a Zoo - Kvapil, Pavel; Račnik, Joško; Kastelic, Marjan; Marková, Jiřina; Murat, Jean-Benjamin; Kobédová, Kateřina; Pittermannová, Pavlina; Budíková, Marie; Sedlák, Kamil; Bártová, Eva (Pathogens (Basel, Switzerland), 2021)
Monitoring of infectious diseases is one of the most important pillars of preventive medicine in zoos. Screening for parasitic and bacterial infections is important to keep animals and equipment safe from pathogens that may pose a risk to animal and human health. Zoos usually contain many different animal species living in proximity with people and wild animals. As an epidemiological probe, 188 animals (122 mammals, 65 birds, and one reptile) from a zoo in Slovenia were examined for selected pathogens. Antibodies to Toxoplasma gondii and Neospora caninum were detected by ELISA in 38% (46/122) and 3% (4/122) of mammals, and in 0% (0/64) and 2% (1/57) of birds, respectively; the reptile (0/1) was negative. A statistically significant difference in T. gondii prevalence was found in Carnivora compared to Cetartiodactyla and primate antibodies to Encephalitozoon cuniculi were detected by IFAT in 44% (52/118) of mammals and 20% (11/56) of birds, respectively; the reptile (0/1) was negative. Herbivores had a higher chance of being infected with E. cuniculi compared to omnivores. Antibodies to Chlamydia abortus and Coxiella burnetii were not detected in any of the 74 tested zoo animals. The sera of 39 wild rodents found in the zoo were also examined; they were negative for all three parasites. The parasite T. gondii was detected by PCR in the tissue of two mute swans (Cygnus olor), three eastern house mice (Mus musculus), one yellow-necked field mouse (Apodemus flavicollis), and one striped field mouse (A. agrarius). Positive samples were genotyped by a single multiplex PCR assay using 15 microsatellite markers; one sample from a mute swan was characterized as type II. This micro-epidemiological study offers a better understanding of pathogens in zoo animals and an understanding of the role of zoos in biosurveillance.
Keywords: serology; toxoplasmosis; neosporosis; encephalitozoonosis; biosurvelliance